High-Throughput Carbon-Capturing Frameworks by Pelleting Hydrochar of Food Waste and its Residual Ash as a Dopant - de Almeida Moreira, Bruno Rafael [UNESP]; de Brito Filho, Armando Lopes [UNESP]; Barbosa Júnior, Marcelo Rodrigues [UNESP]; da Silva, Rouverson Pereira [UNESP] (Springer Nature, 2022)
Studies on converting biomass into an adsorbent often are available from the contemporary academic literature. However, no in-depth systematic investigation exists on the possibility of strategically recycling food waste and the residual ash of its hydrothermal carbonization (HTC) into pellets for the purpose of physical sorption. Therefore, the objective of this study was to transform hydrochar of food waste and its residual ash into high-throughput carbon-capturing frameworks via an integrative HTC-pelletization approach. The pilot-scale manufacturing of adsorbents consisted of carbonizing food waste at 200.00 °C and 1.50 MPa for 2.00 h then pressing its powdery hydrochar, residual ash and spent peanut grain (SPG) together on an automatic pelletizer machine at 75.00-100.00 MPa and 150.00 °C for 90.00 s. The addition of ash as an inorganic dopant structured-up functional gas-binding alkaline sites, such as N, S, SiO2, and Al2O3, onto the surface of pellets. Hence, it enabled them to effectively encapsulate 8.90 mmol CO2 g−1. Co-addition of SPG slightly limited the physisorption to 7.50 mmol CO2 g−1. However, the organic binder, by its powerful stickness, proved useful to enhance the regenerability (>99.00%) of the material over multiple cycles of swinging CO2 to N2 to simulate adsorption and desorption, respectively. Therefore, insights into ramifications of the integrative HTC-pelletization approach are timely. They can provide forward knowledge of relevance to progress in the field’s prominence in elaborating high-throughput physisorption via carbon-to-waste pathways. However, further research is necessary to analyze whether it is feasible or not to bring carbon-capturing pellets into implementation at industrial scale.
Keywords: Agricultural residue; Biomass; Hydrothermal carbonization; Organic waste; Physical sorption